Effect of stretching through the pilates method -- controlled, randomized clinical study. - Stasiu, Vanessa; Braun Ferreira, Luiz Alfredo; Athaus, Martyna; Pereira, Jean; Sluchensci dos Santos, Fernando; Stadler, Patricia; Dranski, Solange; Menna Pereira, Wagner (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Stretching is a therapeutic technique used to increase joint range of motion and flexibility and can be used as a warm-up to prevent injury or improve muscle performance. Pilates is one of the techniques used for such benefits, improving posture, body conditioning, aiding physical and mental control, which main characteristic is resistance work and dynamic stretching. Electromyography (EMG) is the study of muscle function by checking the electrical signal coming from the muscle, as well as the study of the motor unit activity. Objective: To evaluate the electromyographic activity of the hamstring muscles using the surface EMG before and after the application of a stretching protocol through Pilates. Methods: The sample consisted of 30 healthy individuals, 15 participants from the Control Group (CG) and 15 from the Pilates Group (PG), randomly selected from which 18 were selected for analysis. Electromyography was used to evaluate hamstring muscle activity before and after the exercises. For statistical analysis was used the SPSS software version 21, for the normality of the data was used the Kolmogorov-Smirnov test, and for the comparison between the groups was used the T-Student test. The treatment program was performed in the Guairacá Integrated Clinics in Guarapuava-PR, and consisted of ten Pilates exercises during two weekly sessions of forty minute each for five weeks. Results: There was a statistically significant increase (p = 0.00) in the muscle activation amplitude (RMS) of the femoral and semitendinosus biceps muscles after the Pilates stretching protocol in the intervention group when compared with the control group. Conclusion: It was concluded that the Pilates Method exercise protocol directed to hamstring stretching twice a week for five weeks significantly increased muscle activation and that physical inactivity led to a reduction in this activity observed in the control group. It is recommended that further studies be developed analyzing variables not yet studied, aiming to increase scientific knowledge about the influence of stretching through Pilates on muscle performance.